Memfasilitasi Pengelolaan Hutan Kolaboratif Menggunakan Pemodelan Dinamika Sistem - Purnomo, Herry (Jurnal Manajemen Hutan Tropika, 2004)
Increasing forest degradation and community poverty are painful. Meanwhile, the behaviors of forest resources and their stakeholders are poorly understood. Systems dynamics is an approach, which is able to capture the complexity, dynamics and uncertainty of the management of forest resources and to develop future scenarios. This approach is not sufficient, however, if it is not placed in the multi-stakeholder context, where each stakeholder plays an important role. This paper discusses the use of systems dynamic as a tool to facilitate multi-stakeholder process and social learning towards sustainable and equitable forest management. A case study was conducted at Darmaga Experimental Forest, Bogor using software ‘The Bridge’. ‘The Bridge’ facilitated the Darmaga Forest stakeholders to articulate their future vision, strategy and its indicators. Then, they were converted into a systems dynamic model where the future scenarios could be drawn and learned.